Quality and the Great Trade Collapse - Chen, Natalie (IMF Working Papers; Working Paper ;, 2016)
We explore whether the global financial crisis has had heterogeneous effects on traded goods differentiated by quality. Combining a dataset of Argentinean firm-level destination-specific wine exports with quality ratings, we show that higher quality exports grew faster before the crisis, but this trend reversed during the recession. Quantitatively, the effect is large: up to nine percentage points difference in trade performance can be explained by the quality composition of exports. This flight from quality was triggered by a fall in aggregate demand, was more acute when households could substitute imports by domestic alternatives, and was stronger for smaller firms' exports.